2013 IEEE 9th International Conference on Emerging Technologies (ICET) 2013
DOI: 10.1109/icet.2013.6743502
|View full text |Cite
|
Sign up to set email alerts
|

Computational intelligence and safe reduction of test suite

Abstract: Systems are frequently regression tested during the maintenance phase due to corrective, preventive, adaptive or perfective actions. Regression testing is used to prevent the undesirable effects of these changes on the previously tested version. Due to these changes, new test cases become part of the test suite making it huge and inefficient for 'retest all' strategy. The ultimate solution of this problem is optimization or reduction of the test suite. Computational Intelligence (CI) based approaches like evol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…While in 2013, [32][33] use some CI based approaches in order to optimize the test suite and analyze the test suite for safe reduction which can be estimated using control flow graphs. Test cases of optimal solutions are traversed on these graphs and it is found that only fuzzy logic is safe while other approaches will be inadequate for regression testing.…”
Section: Fuzzy Logicmentioning
confidence: 99%
“…While in 2013, [32][33] use some CI based approaches in order to optimize the test suite and analyze the test suite for safe reduction which can be estimated using control flow graphs. Test cases of optimal solutions are traversed on these graphs and it is found that only fuzzy logic is safe while other approaches will be inadequate for regression testing.…”
Section: Fuzzy Logicmentioning
confidence: 99%